Organizational obliviousness : entrenched resistance to gender integration in the military - Doan, Alesha E., 1972-; Portillo, Shannon (Cambridge : Cambridge University Press, 2019)
Exploring efforts to integrate women into combat forces in the military, we investigate how resistance to equity becomes entrenched, ultimately excluding women from being full participants in the workplace. Based on focus groups and surveys with members of Special Operations, we found most of the resistance is rooted in traditional gender stereotypes that are often bolstered through organizational policies and practices. The subtlety of these practices often renders them invisible. We refer to this invisibility as organizational obliviousness. Obliviousness exists at the individual level, it becomes reinforced at the cultural level, and, in turn, cultural practices are entrenched institutionally by policies. Organizational obliviousness may not be malicious or done to actively exclude or harm, but the end result is that it does both. Throughout this Element we trace the ways that organizational obliviousness shapes individuals, culture, and institutional practices throughout the organization.
Title from publisher's bibliographic system (viewed on 30 May 2019).
Keywords: United States -- Armed Forces -- Women; United States -- Armed Forces -- Personnel management